HEAT-TRANSFER FROM CONTINUOUSLY MOVING MATERIAL IN CHANNEL FLOW FOR THERMAL-PROCESSING - KANG, BH; JALURIA, Y (AMER INST AERONAUT ASTRONAUT, 1994)
The conjugate mixed convection and conduction transport that arises due to the continuous movement of a heated material in a parallel channel flow of a cooler fluid has been numerically investigated. The basic problem studied is of interest in several manufacturing processes, ranging from crystal growing and continuous casting to extrusion, hot rolling, wire drawing, and glass fiber drawing. A flat plate, or sheet, moving in a wide channel is considered in this article. A two-dimensional, steady circumstance, with laminar flow in the fluid, is assumed. The full, elliptic, governing equations are solved, employing finite difference techniques. Numerical results are obtained for various values of the important physical parameters such as plate speed U(s), the forced flow velocity in the channel U(infinity), and temperature T0 of the material upstream of the cooling region. The effect of the geometry, or configuration, of the system is also investigated. The results obtained indicate that, as expected, the effect of thermal buoyancy is more significant when the plate is moving vertically upward than when it is moving horizontally, and also when the forced flow velocity is small. A strong forced flow leads to a fairly uniform velocity distribution across much of the channel. The plate speed substantially affects the overall heat transfer rate. Although this work is focused on convective cooling of a heated moving material, the basic considerations and many of the results can easily be extended to a moving material which is being heated through convection, i.e., in a heat treatment process.
Keywords: NUMERICAL-SIMULATION; TRANSPORT; PLATE